Return - Becker, Aaron, 1974- (Somerville, Massachusetts : Candlewick Press, 2016)
Failing to get the attention of her busy father, a lonely girl turns back to a fantastic world for friendship and adventure. It’s her third journey into the enticing realm of kings and emperors, castles and canals, exotic creatures and enchanting landscapes. This time, it will take something truly powerful to persuade her to return home. Caldecott Honor winner Aaron Becker delivers a suspenseful and moving climax to his wordless trilogy, an epic that began with the award-winning Journey and continued with the celebrated follow-up Quest.
Keywords: Doors -- Juvenile fiction; Drawing -- Juvenile fiction; Magic -- Juvenile fiction; Stories without words; Picture books for children; Doors -- Fiction; Drawing -- Fiction; Magic -- Fiction; Kings, queens, rulers, etc. -- Fiction; Stories without words; Fantasy fiction